Aplicação de métodos para avaliação de Planos de Saneamento: estudo de caso em cinco municípios de pequeno porte - Albuquerque, Leilane Renovato (Universidade Federal de São Carlos, 2019)
Brazil faced accelerated urbanization without sanitation planning. This process evidenced deficiencies in the sanitation sector, directly affecting the quality of life and health of the population and generating impacts to the environment. Given this scenario, the planning of service delivery and the achievement of efficiency and effectiveness in their management become the premises for the search for universal access. Federal Law 11445/2007 defines the Municipal Basic Sanitation Plan (PMSB) as the main planning and management tool for the sector. The objective of the present study was to evaluate five PMSBs based on indicators and indices. The research included a review of the literature on sanitation plans (stage 1), reading and interpretation of five selected plans (step 2), application of a method to evaluate the content of the plans (Quality Index - IQ) and their performance (Audit Index - IA) in relation to the defined goals and objectives. The method proposed by the Ministry of Cities was applied in a comparative way to the selected one, in order to observe the potentialities and limitations of each instrument (step 3). The intention of the study was to observe deficient information that deserves to be detailed in the plans. The main results indicated that the documents analyzed partially meet the requirements of the Sanitation Law. The IQ has identified that some issues (social participation, service diagnosis, goals, actions and environmental education) are adequately addressed in the content of the plans. Institutional development presented itself as a weak point in all evaluated plans. The Ministry of Cities method has identified that all the documents analyzed need improvement (compatibility with other plans, absence of schematic drawings or sketches for technical engineering solutions for sanitation service systems and identification of the low-income population).
Application of methods for evaluation of Sanitation Plans: a case study in five small municipalities
Keywords: Planos municipais; Saneamento; Gestão urbana; Indicadores; Universalização; Municipal plans; Sanitation; Urban management; Indicators; Universalization; ENGENHARIAS